Inferring reporting biases in hedge fund databases from hedge fund equity holdings - Vikas Agarwal; Vyacheslav Fos; Wei Jiang (University of Cologne, Centre for Financial Research (CFR), 2012)
This paper formally analyzes the biases related to self-reporting in hedge fund databases by matching the quarterly equity holdings of a complete list of 13F-filing hedge fund companies to the union of five major commercial databases of self-reporting hedge funds between 1980 and 2008. We find that funds initiate selfreporting after positive abnormal returns which do not persist into the reporting period. Termination of selfreporting is followed by both return deterioration and outflows from the funds. The propensity to self-report is consistent with the trade-offs between the benefits (e.g., access to prospective investors) and costs (e.g., partial loss of trading secrecy and flexibility in selective marketing). Finally, returns of self-reporting funds are higher than that of non-reporting funds using characteristic-based benchmarks. However, the difference is not significant using alternative choices of performance measures.
Keywords: 330